If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + 4 = 8b + -13 Combine like terms: 11 + 4 = 15 15 = 8b + -13 Reorder the terms: 15 = -13 + 8b Solving 15 = -13 + 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. 15 + -8b = -13 + 8b + -8b Combine like terms: 8b + -8b = 0 15 + -8b = -13 + 0 15 + -8b = -13 Add '-15' to each side of the equation. 15 + -15 + -8b = -13 + -15 Combine like terms: 15 + -15 = 0 0 + -8b = -13 + -15 -8b = -13 + -15 Combine like terms: -13 + -15 = -28 -8b = -28 Divide each side by '-8'. b = 3.5 Simplifying b = 3.5
| -18-11r=-21 | | 24=-12w | | r-2s=sinx*cosy | | 3m+5=8m+105 | | 3m+5=8m-1-5 | | 4+3n=n-7+n | | 3+5m=8m-105 | | 3x+5=3(2x+4)+3x | | -79+x+9x=41 | | .04x+.2(6-x)=.08(6) | | -3(4t-2)+5t=6t-8 | | D=5d-6 | | 1=.5x*3.61 | | 8+2(3x-2)=5 | | -1(n*n+3)=2(-4*3) | | 240=128t-16t^2 | | 1/2x-1/5=-10 | | 2(0.36x+11d)= | | -5(x+3)-8=-23 | | p=0.007*4600 | | -x+2x-12=5 | | 16x-1y= | | -1(3*3)=2(-4*3) | | 23x-5+21x+5=23x-5+21x+5s | | 15=-3(n-2)-6 | | y+8=-5(x-3) | | X(2+9x)=0 | | 6m-4=7m+7-m | | -8(9x+9)+6= | | 15-(4v+4)=-4v-11 | | 5x+x+60=90 | | 6+(3+b)= |